Criminal law and organized crime: An analysis from the perspective of Niklas Luhmann's systems theory - Vázquez Pérez, Eduardo Daniel (2021)
This research takes up the vision of the German jurist Niklas Luhmann on the self-referentiality of systems; however, it places greater emphasis on the autopoietic systems aspect. The aim of this article is to demonstrate how the effective applicability of the legal-criminal norm can combat corruption in Mexico, rescuing the democratic state and through the evaluation of the proposals by the current administration, contained in the Development Plan 2019-2024.